What Do They Want From My Life? Parent-Child Relationships as Perceived by Druze Adolescents in Israel. Issue 3 (May 2019) - Abbas, Randa; Pataki, Sherri P.; Vaknin-Nusbaum, Vered; Ilaiyan, Salman
This research examined Druze adolescents' perception of their relationships with parents in Israel. Israeli Druze is a small group accounting for only 2% of Israel's population. The Druze society is patriarchal; it demands absolute loyalty to the values of religion, family, and clan. Our goal was to explore the impact of increasing intercultural contact with modern Israeli society and the outside world on parent-child relationships in a traditional society that demands absolute loyalty and obedience to elders. The researchers used the phenomenological approach to understand parent-child relationships from the perspective of the adolescents themselves. Twelve Druze adolescents, six females and six males ranging in age from 16 to 18, completed a semi-structured interview in which they were asked to describe their relationships with parents. Participants were prompted to describe a recent conflict, if any, and the way in which the conflict was resolved, as well as a positive and a negative interaction with parents in the past year. Thematic analyses revealed intergenerational conflict related to perceived acculturation gaps. Other consistent themes portrayed supportive parent-child relationships and the adolescents' commitment to Druze heritage. Overall, findings suggest that although increasing exposure to modern society may lead to intergenerational conflict, Druze adolescents remained grounded in supportive family relationships and their religious heritage.